SIMRS Analysis of Hospital Management Information System Implementation In Manembo-Nembo General Hospital, Bitung City - Lumingkewas, Pitter Handry; Umboh, Adrian; Manampiring, Aaltje E. (Gema Wiralodra, 2023)
Ministry of Health of the Republic of Indonesia Regulation Number 82 of 2013, chapter 3, states that every hospital is obliged to implement the Hospital Management Information System (SIMRS). SIMRS is a collection of processes implemented to help improve the efficiency and effectiveness of healthcare organizations in carrying out their functions and achieving their goals. This qualitative study uses a case study approach using the depth-interview method. The research was conducted at the Manembo Nembo General Hospital, Bitung  City, in North Sulawesi Province, from March to July 2022. The sample consisted of 5 informants, including the hospital director, head of the medical services department, head of SIMRS installation, operator, and healthcare recipient. Data analysis in this research will use content analysis by Miles and Huberman, and the validity of the research results will be ensured through source triangulation and methods. The research findings reveal that the implementation of SIMRS has the infrastructure component available in terms of hardware, but it has not been fully implemented in all departments (outpatient, inpatient, and nutrition), thus not being effective and efficient. Additionally, the implementation of SIMRS in terms of the network component is available but not fully connected to all departments (pharmacy, radiology, and laboratory), and the application system already uses open source software but has not been integrated into all departments due to a limited number of competent personnel in that field. Furthermore, the implementation of SIMRS in terms of the human resources component is sufficient, but the qualification and competence of personnel in developing open source applications for other departments, such as connecting services such as telemedicine and electronic medical records, as well as integrated applications (eg, Sisrute , Satu Sehat, e-KTP with the population and civil registration agency, BPJS Health, SIMDA, and LKPP) still need improvement. The procedures are well-implemented based on the tasks and functions, but the competency in computer information technology needs to be enhanced for the optimal implementation of SIMRS. In conclusion, the performance of SIMRS in the Manembo Nembo General Hospital of Bitung City from the requirements regarding infrastructure, network, and human resources components are available and eligible.